METODE GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA DI MA ROUDLOTUS SHOLIHIN KECAMATAN AIR HITAM KABUPATEN LAMPUNG BARAT TAHUN AJARAN 2023/2024 - Ulul Fahmi (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
Abstract Morals have the function of making human behavior more civilized and being able to identify various life problems, good or bad according to the applicable norms. The purpose of this study is to determine the role of Islamic Religious Education (PAI) teachers in fostering the morals of students at SMAN I Kandat. This study uses a type of field research conducted to obtain accurate data by directly visiting the research object. The method used is descriptive qualitative. The research results include providing role models, namely moral and spiritual role models. Through habituation, namely habituation of morning time getting off the motorbike, shaking hands with teachers, praying, being honest, praying in congregation, giving alms, and dressing well. Providing advice, namely giving advice to dress according to Islamic law, behave in a way that reflects good morals, and pray. And the implementation of written and unwritten rules and regulations.